The The Relationship between Leadership Management and Employee Performance and Motivation at the Semen Padang Hospital Outpatient Pharmacy Installation - Muthia, Gabila Heira; Semiarty, Rima; Nurdin, Aguswan (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2023)
Leadership is a sociological phenomenon to mobilize employees in achieving effective and efficient performance. In realizing maximum employee performance, high work motivation is needed. Employees who have high work motivation will provide good performance. The role of the leader is very large in creating a work atmosphere with high work motivation. Leadership management practices also occur in the Semen Padang Hospital outpatient pharmacy installation. With the challenge of a high workload, a leader must be able to influence the work motivation of his subordinates in order to provide maximum performance. This study aims to determine the relationship between leadership and employee performance, the relationship between leadership and employee work motivation and the relationship between work motivation and employee performance in the Semen Padang Hospital outpatient pharmacy installation. This research design is crossectional using causal studies. The research was conducted through quantitative methods and used Partial Least Square statistical analysis to test the relationship between variables. This study used total sampling in the sampling technique. Based on the results of the study, it was found that leadership has no significant effect on employee performance. Leadership has a significant influence on work motivation and work motivation has a significant relationship with employee performance. Keywords: Leadership, Employee Performance, Work Motivation.